SKOR ISAN SEBAGAI PREDIKTOR IN-HOSPITAL MORTALITY PADA PASIEN DENGAN STROKE-ASSOCIATED PNEUMONIA - Mara Ditta, Adist Azizy; Gofir, Abdul; Satiti, Sekar; Hanif, Faishal (PERDOSNI, 2024)
Introduction: Stroke-associated pneumonia (SAP) is attributed as the most common cause of death in acute stroke. ISAN score is a potential tool for predicting SAP in acute stroke care since it is easy to use. Several clinical risk such as age and pre-stroke disability has been proposed to contribute mortality in SAP patients. Aims: This study aims to determine the relationship between ISAN score and in-hospital mortality in acute stroke patients at RSUP Dr. Sardjito. Methods: This study is an analytic observational study with a retrospective cohort design using data from the stroke registry of the Stroke Unit of RSUP Dr. Sardjito from 2021 - 2023. Patients who were clinically diagnosed with SAP at the time of acute phase stroke treatment were included in the study. ISAN scores were divided into 0-5, 6-10, 11-14, and >14 with the interpretation of low, medium, high, and very high respectively. The data was analysed using SPSS v22.. Results: A total of 147 stroke patients with SAP (55% male, mean age 64.9 Ã‚Â± 13.4 years) were included in this study. Death occurred in 61 study subjects and was more prevalent in the high ISAN group (n=30). On bivariate analysis, mortality was significantly associated with ISAN score (p=0.002), gender (p=0.003) and NIHSS score (p=0.002). High ISAN scores have been associated with mortality of stroke patients with SAP, according to multivariate analysis. (aOR=3.94, IK95% 1.31-11.84, p=0.015). Discussion: A high ISAN score at admission is significantly associated with mortality of stroke patients with SAP. Keywords: Pneumonia, stroke, mortality, acute stroke, ISAN score